Decision Support System For The Best Junior High School Using The Distance To The Ideal Alternative (Dia) Method At The Education And Culture Office Of The City Of Bengkulu - Putra, Anton Pradana; Sartika, Devi; Lianda, Deri (Jurnal Media Computer Science, 2024)
The assessment of the best private schools aims to improve the quality of school activities. The obstacle faced is the difficulty of evaluating school assessments objectively because many criteria are not well organized for schools. To overcome these obstacles, a decision support system using the Distance To The Ideal Alternative (DIA) method is needed to be utilized as a tool in supporting the decision-making process. The system implementation uses Visual Basic 2010 programming language and the method used in this research is the waterfall method. From the test results, it can be concluded that the teacher performance assessment using Distance To The Ideal Alternative (DIA) can be done well by taking the top number of schools from the Distance To The Ideal Alternative ranking process which can then be reported in the form of a school assessment report.